High time-resolved measurement of stable carbon isotope composition in water-soluble organic aerosols: method optimization and a case study during winter haze in eastern China - Zhang, Wenqi; Zhang, Yan-Lin; Cao, Fang; Xiang, Yankun; Zhang, Yuanyuan; Bao, Mengying; Liu, Xiaoyan; Lin, Yu-Chi (Atmospheric chemistry and physics, 2019)
Water-soluble organic carbon (WSOC) is a significant fraction of organic carbon (OC) in atmospheric aerosols. WSOC is of great interest due to its significant effects on atmospheric chemistry, the Earth's climate and human health. The stable carbon isotope (δ13C) can be used to track the potential sources and investigate atmospheric processes of organic aerosols. However, the previous methods measuring the δ13C values of WSOC in ambient aerosols require a large amount of carbon content, are time-consuming and require labor-intensive preprocessing. In this study, a method of simultaneously measuring the mass concentration and the δ13C values of WSOC from aerosol samples is established by coupling the GasBench II preparation device with isotopic ratio mass spectrometry. The precision and accuracy of isotope determination is better than 0.17 ‰ and 0.5 ‰, respectively, for samples containing WSOC amounts larger than 5 µg. This method is then applied for the aerosol samples collected every 3 h during a severe wintertime haze period in Nanjing, eastern China. The WSOC values vary between 3 and 32 µg m−3, whereas δ13C−WSOC ranges from −26.24 ‰ to −23.35 ‰. Three different episodes (Episode 1, Episode 2 and Episode 3) are identified in the sampling period, showing a different tendency of δ13C−WSOC with the accumulation process of WSOC aerosols. The increases in both the WSOC mass concentrations and the δ13C−WSOC values in Episode 1 indicate that WSOC is subject to a substantial photochemical aging during the air mass transport. In Episode 2, the decline of the δ13C−WSOC is accompanied by the increase in the WSOC mass concentrations, which is associated with regional-transported biomass burning emissions. In Episode 3, heavier isotope (13C) is exclusively enriched in total carbon (TC) in comparison to WSOC aerosols. This suggests that the non-WSOC fraction in total carbon may contain 13C-enriched components such as dust carbonate, which is supported by the enhanced Ca2+ concentrations and air mass trajectory analysis. The present study provides a novel method to determine the stable carbon isotope composition of WSOC, and it offers a great potential to better understand the source emission, the atmospheric aging and the secondary production of water-soluble organic aerosols.